Hidrotechnics Prevent Vibrations that Occur in Constructions - Muminov Oybek Alisher ugli; Sulaymonova Durdona Boburjonovna (Research Parks Publishing LLC, 2022)
The preservation of the hydrotechnical structures from the vibration phenomenon is due to the Reserve work, which is carried out taking into account the circumstances associated with an increase or decrease in the flow in the project, an increase in the flood arrival time, a complete cessation of the water discharge pipeline, these works are completely received from the vibration phenomenon and the